Prior antibiotic exposure and risk of type 2 diabetes among Veterans. Issue 1 (February 2019) - Davis, P. Jordan; Liu, Mengling; Alemi, Farrokh; Jensen, Ashley; Avramovic, Sanja; Levy, Esther; Hayes, Richard B.; Schwartz, Mark D.
Highlights: Exposure to commonly used antibiotics increased the risk of type 2 diabetes by 13%. This risk of diabetes increased with repeated exposure, varying by antibiotic class. Risk linked with antifungal, macrolide, penicillin, quinolone & tetracycline drugs. The mean daily dose and cumulative dose (mg) of antibiotic increased diabetes risk. Abstract: Background: Exposure to antibiotics may increase the risk of type 2 diabetes. Veterans are at increased risk for diabetes and for exposure to antibiotics. Objective: To determine the impact of antibiotic exposure for risk of diabetes. Design: Retrospective cohort study. Participants: Veterans at the New York Harbor Healthcare System enrolled in primary care, 2004–2014, with ≥2 glycosylated hemoglobin test results <6.5%. Main measures: The primary exposure was any antimicrobial prescribed >6 months prior to the date of diabetes diagnosis, loss to follow-up, death, or the end of the study, measured as the number of courses of antimicrobial prescriptions filled and the mean daily dose (MDD). The primary outcome was incident diagnosis of diabetes through 2014, defined ≥2 ICD-9 codes for diabetes or ≥2 prescriptions of diabetes medications, other than metformin. Cox proportional hazards regression was used to model antimicrobial medications, demographic and anthropometric measures, and comorbid cardiovascular conditions to incident diabetes. Models incorporated time varying covariates of antimicrobial medication and MDD to analyze associations by antimicrobial class. Key results: Among 14, 361 Veterans, 9922 (69.1%) were prescribed any antimicrobial medication during the study period. 1413 (9.8%) individuals developed type 2 diabetes. Increased risk of diabetes was associated with >1 prescription (HR 1.13 [1.01–1.26]) compared to none. Time varying analysis of the total number of cumulative courses prescribed showed increased diabetes risk for cephalosporin (HR 1.17 [1.04–1.31]), macrolide (HR 1.08 [1.03–1.13]) and penicillin (HR 1.05 [1.02–1.07]). MDD showed increased risk per 100-unit (mg) increase in antibiotic exposure from (HR 1.05 [1.02–1.08]) for sulfonamide to (HR 1.70 [1.51–1.92]) for cephalosporin. Conclusion: Any and repeated exposure to certain antibiotics may increase diabetes risk among Veterans. Results from this study add to the growing evidence suggesting that antibiotic exposure increases risk for diabetes. Antibiotic stewardship may be enhanced by better understanding this risk, and may lower the incidence of diabetes in populations at risk.